Branding Positioning, Marketing Kit, and Marketing Plan : Praktik Pengabdian di Kafe Bangsal Kopi Bantul Yogyakarta - Gulam Hazmin; Adi Prasetyo; Aditya Wahana; Nashruddin Achmad; Kevin Gray Dasmasela; Ventiratna Nur’aini (Jurnal Pengabdian UNDIKMA, 2023)
This service is to increase the brand awareness of cafe Bangsal Kopi through the creation of a video profile, marketing kit and marketing plan. The implementation method of this service involves educating and assisting. The evaluation instruments used in this activity include observation and interviews, which are analyzed descriptively. The results of this service show that Bangsal Kopi can consistently and effectively manage content on Instagram by utilizing the prepared marketing plan. The visually appealing social media theme templates help strengthen the visual appeal and brand identity of Bangsal Kopi. The created video profile provides a comprehensive overview of the cafe, menu, and customer experience, maintaining the emotional connection with potential visitors. The analysis of social media performance before and after the implementation of the strategy indicates an increase in followers, engagement, and visitors. This suggests that the marketing efforts have successfully enhanced brand awareness, interaction, and interest in Bangsal Kopi. It is also expected that there will be an increase in revenue associated with the rise in the number of visitors and higher engagement levels.